anonymous
  • anonymous
How do you rewrite an equation from point-slope form to slope-intercept form? And from slope-intercept form, how do you convert to standard form?
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
jamiebookeater
  • jamiebookeater
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
If I remember it properly point-slope for is in terms of x= and slope-intercept form is in terms of y=
Hero
  • Hero
Begin by writing an equation in point slope form: (y - y1) = m(x - x1). Then manipulate it until you have the form y = mx + b. Then, go a step further and manipulate it until you have the form ax + by = c For example, suppose you're given the point (x,y) = (2,5) and the slope m = 3. Rewriting this in point slope form produces: (y - 2) = 3( x -5) . To re-write this equation in slope-intercept form, manipulate the equation as follows: (y - 2) = 3(x - 5) y - 2 = 3x - 15 y = 3x - 15 + 2 y = 3x - 13 This last form, y = 3x - 13 is the slope-intercept form y = mx + b. Finally, to put this equation in standard form ax + by = c, manipulate the equation as follows: y = 3x - 13 13 = 3x - y 13 = 3x - 1y 3x + (-1)y = 13 The last form, 3x + (-1)y = 13 is the standard form ax + by = c.

Looking for something else?

Not the answer you are looking for? Search for more explanations.